2023
DOI: 10.3389/fmed.2023.1152587
|View full text |Cite
|
Sign up to set email alerts
|

CovAID: Identification of factors associated with severe COVID-19 in patients with inflammatory rheumatism or autoimmune diseases

Abstract: IntroductionAutoimmune/inflammatory rheumatic diseases (AIRDs) patients might be at-risk of severe COVID-19. However, whether this is linked to the disease or to its treatment is difficult to determine. This study aimed to identify factors associated with occurrence of severe COVID-19 in AIRD patients and to evaluate whether having an AIRD was associated with increased risk of severe COVID-19 or death.Materials and methodsTwo databases were analyzed: the EDS (Entrepôt des Données de Santé, Clinical Data Wareho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 69 publications
(111 reference statements)
0
6
0
1
Order By: Relevance
“…It seems that the risk only affects patients with a corticosteroid dose ≥10 mg/day [53]. Interestingly, treatment with leflunomide and methotrexate was significantly associated with a better outcome [49]. The TNF-alpha antagonists do not seem to be associated with severe COVID-19 in this and other studies [44,49,53].…”
Section: Covid-19 Severity In Patients With Sarcoidosis?mentioning
confidence: 51%
See 3 more Smart Citations
“…It seems that the risk only affects patients with a corticosteroid dose ≥10 mg/day [53]. Interestingly, treatment with leflunomide and methotrexate was significantly associated with a better outcome [49]. The TNF-alpha antagonists do not seem to be associated with severe COVID-19 in this and other studies [44,49,53].…”
Section: Covid-19 Severity In Patients With Sarcoidosis?mentioning
confidence: 51%
“…For example, the study conducted by Chevalier et al analyzed 1213 patients with autoimmune/inflammatory rheumatic diseases with COVID-19 from two French national databases: the EDS (Entrepôt des Données de Santé, including all patients followed in Paris university hospitals) and the French multicenter COVID-19 cohort French Rheumatic and Musculoskeletal diseases (RMDs). Among the 64 patients with both sarcoidosis and COVID-19, the study found that sarcoidosis was an independent factor for severe COVID-19 (i.e., ICU admission and/or death) in the multivariate analysis (aOR = 5.19, 2.15-12.3), along with other factors, such as older age, interstitial lung disease, arterial hypertension, and obesity [49].…”
Section: Covid-19 Severity In Patients With Sarcoidosis?mentioning
confidence: 93%
See 2 more Smart Citations
“…Случай смерти от COVID-19 был ранее описан отечественными авторами у пациента, страдавшего в течение трех лет саркоидозом со стабильным течением, но с гипертонической болезнью, концентрической гипертрофией миокарда, хронической ишемической болезнью сердца со стенозирующим атеросклерозом коронарных артерий и кардиосклерозом [20]. Наблюдательные исследования, проведенные в различных медицинских центрах, в большинстве случаев свидетельствовали о благоприятном течении заболеваний при их сочетании, невысокой распространенности COVID-19 среди пациентов с саркоидозом, а ключевыми факторами риска тяжелого течения COVID-19 для пациентов с саркоидозом были нарушение функции легких, внелегочные поражения, сопутствующие заболевания, развившиеся до пандемии, и продолжаю щаяся иммуносупрессивная терапия саркоидоза [21][22][23].…”
Section: Covid-19unclassified